The associations between biological father involvement (quantity and quality) and family support with adult child well-being - Williams, George Russell (Kansas State University, 2016)
The purpose of this dissertation was to investigate factors related to quantity and quality of biological father involvement in non-intact families and family support and their association with young adult child outcomes. The independent variables examined were the biological father's number of years living with his child, early, middle and late developmental periods present, number of transitions, and relationship quality with the young adult child during childhood. The dependent variables were related to sexual health and five distinct domains that have emerged from the research literature: 1) education, 2) economic, 3) physical, 4) social, and 5) emotional. This dissertation drew on a subsample of the 2,988 respondents of the New Family Structures Study (NFSS). Biological fathers were examined from non-intact families (n = 1793) of which 1,080, lived with their child for at least part of a year. The Father Adult-child Involvement Relationship Outcomes (FAIRO) Model was developed with current literature and theory to form quantity and quality father involvement hypotheses and test those using mean comparisons, bivariate, and multivariate analyses. This study detected weak to moderate positively statistically significant associations between the quantity and quality of the biological father involvement in the non-intact families and young adult child outcomes. The results seemed to indicate the importance of the role of the father; even in a non-intact family where the father spends time apart from his children, he is still able to influence the outcomes of his children. The findings pointed to the need for further research into fatherhood transitions, early involvement, and the salient influence of family support. This research takes a small step in examining quantity and quality father involvement associations on young adult outcomes to make an incremental contribution to the research, theory, and practice of father involvement that may benefit the future well-being of children.
Keywords: Father involvementFatherhood; Fathering